SOME REFLECTIONS ON THE PRINCIPLE OF LEGAL CERTAINTY - Yusupov Ilkhomjon Ibodillaevich (Scholar Express Journals, 2024)
This article presents some considerations regarding the specifics of the principle of legal accuracy. At the same time, reasonable opinions are given on the application of the principle of legal accuracy in the field of legislative activity. The reasoned opinions of scientists on the principle of legal certainty are also given.
Keywords: European; principle; primacy of law; constitutionality